NON-R&D INNOVATION AND INNOVATION PERFORMANCE: A CONCEPTUAL FRAMEWORK - widya hastuti afris (BJRM (Bongaya Journal of Research in Management), 2020)
A number of studies in the innovation literature have examined the construct of non-R&D innovation. These research generally revealed a positive link between non-R&D innovation and innovation performance. As far as this paper is concerned, non-R&D was specifically evaluated in the context of small and medium-sized enterprises (SMEs). An in-depth review of the extant literature was performed to develop a conceptual framework by exploring the major antecedents of non-R&D, the EO-non-R&D innovation–performance relationship, and the key mediators and moderators of this relationship. This paper also examined several studies of SMEs with respect to various aspects of this framework in addition to providing suggestions for future research in order to understand more thoroughly on how non-R&D influences SME innovation performance.